IOIBD technical review on endoscopic indices for Crohn's disease clinical trials. Issue 9 (9th September 2015) - Vuitton, L; Marteau, P; Sandborn, W J; Levesque, B G; Feagan, B; Vermeire, S; Danese, S; D'Haens, G; Lowenberg, M; Khanna, R; Fiorino, G; Travis, S; et al.
Abstract : Background: Crohn's disease (CD) is a chronic disabling and progressive IBD. Only strategies looking beyond symptoms and based on tight monitoring of objective signs of inflammation such as mucosal lesions may have the potential for disease modification. Endoscopic evaluation is currently the gold standard to assess mucosal lesions and has become a major therapeutic endpoint in clinical trials. Several endoscopic indices have been proposed to evaluate disease activity; unvalidated and arbitrary definitions have been used in clinical trials for defining endoscopic response and endoscopic remission in CD. Methods: In these recommendations from the International Organization for the Study of Inflammatory Bowel Disease, we first reviewed all technical aspects of available endoscopic scoring systems in the literature. Second, in order to achieve consensus on endoscopic definitions of remission and response in trials, a two-round vote based on a Delphi method was performed among 14 specialists in the field of IBDs. Results: At the end of the voting process, the investigators ranked first a >50% decrease in Simple Endoscopic Score for Crohn's Disease (SES-CD) or Crohn's Disease Endoscopic Index of Severity for the definition of endoscopic response, and an SES-CD 0–2 for the definition of endoscopic remission in CD. All experts agreed on a Rutgeerts' score i0–i1 for the definition of endoscopic remission after surgery.